Increase Repurchase Intention Through Customer Satisfaction and Customer Trust (DANA User Survey Study in Serang City) - Novaria, Vidy Kun; Ramdansyah, Agus David; Nupus, Hayati (Sahabat Publikasi, 2025)
This study was conducted with the aim of developing a basic theoretical model and a new empirical research model to resolve the gap in previous research results regarding perceived value in increasing repurchase intention through customer satisfaction and customer trust felt by a company. The object of this study is DANA users in the city of Serang. The sampling technique in this study used a non-probability sampling technique, namely the accidental sampling method. With the population size not known for certain and a sample of 160 people or respondents. The data analysis technique used Partial Least Square (PLS) with smartPLS 3.0 software. The results of the study showed that: 1) Perceived Value has a positive and significant effect on Repurchase Intention; 2) Perceived Value has a positive and significant effect on Customer Satisfaction; 3) Perceived Value has a positive and significant effect on Customer Trust; 4) Customer Satisfaction has a positive and significant effect on Repurchase Intention; 5) Customer Trust has a positive and insignificant effect on Repurchase Intention. 6) Customer Satisfaction is able to mediate between Perceived Value and Repurchase Intention through partial mediation; 7) Customer Trust is not able to mediate between Perceived Value and Repurchase Intention through zero mediation.